Absence and Memory in Colonial American Theatre Fiorelli's Plaster - Johnson, O.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2006)
History, they say, has a filthy tongue. In the case of colonial theatre in America, what we know about performance has come from the detractors of theatre and not its producers. Yet this does not account for the flourishing theatrical circuit established between 1760 and 1776. This study explores the culture's social support of the theatre.
Keywords: Theater—History.; Theater; America—History.; Performing arts; Europe—History—1492-.; Theatre History; Theatre and Performance Studies; History of the Americas; Performing Arts; History of Early Modern Europe